2006
DOI: 10.1111/j.1365-2222.2006.02442.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of rBet v 1‐induced basophil histamine release with specific immunotherapy ‐induced serum immunoglobulin G: no evidence that FcγRIIB signalling is important

Abstract: We suggest that at least in birch pollen SIT, the contribution of FcgammaRIIB-mediated inhibitory signalling to SIT-IgG-induced inhibition of human basophil histamine release is of minor importance. The main contributor to the inhibitory effect of SIT-induced IgG seems to be blocking of the allergen-IgE interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 46 publications
(53 reference statements)
1
46
0
1
Order By: Relevance
“…It has been reported that concomitant binding of IgG and IgE antibodies to the same allergen may down-regulate effector cell responses through co-cross-linking of IgE and IgG receptors (Malbec and Daeron 2007;Mertsching et al 2008). These studies have been performed mainly in murine models whereas for human immunotherapy studies no evidence for down-regulation of effector cell activation by co-cross-linking has been found so far (Ejrnaes et al 2006). Moreover, allergen-specific IgG antibodies are responsible for the reduction of IgE-facilitated antigen presentation by preventing the binding of allergen to APCbound IgE antibodies resulting in decreased T cell activation.…”
Section: Beneficial Role Of Allergen-specific Blocking Igg Antibodiesmentioning
confidence: 98%
“…It has been reported that concomitant binding of IgG and IgE antibodies to the same allergen may down-regulate effector cell responses through co-cross-linking of IgE and IgG receptors (Malbec and Daeron 2007;Mertsching et al 2008). These studies have been performed mainly in murine models whereas for human immunotherapy studies no evidence for down-regulation of effector cell activation by co-cross-linking has been found so far (Ejrnaes et al 2006). Moreover, allergen-specific IgG antibodies are responsible for the reduction of IgE-facilitated antigen presentation by preventing the binding of allergen to APCbound IgE antibodies resulting in decreased T cell activation.…”
Section: Beneficial Role Of Allergen-specific Blocking Igg Antibodiesmentioning
confidence: 98%
“…The inhibitory effect of the BF may be mediated by antibodies (sIgG, sIgG4 or sIgA) and several authors have demonstrated that IgG or IgG4 contained in sera taken from patients under VIT showed an inhibitory activity on the basophil response [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The inhibition could be caused by a direct inhibition of the allergen-IgE interaction or through coaggregation of the inhibitory FcγRIIB and FcεRI as demonstrated in an artificial system by Kepley et al [110]. However using sera from SIT-treated patients, we were not able to demonstrate a contribution of FcγRIIB activation to the inhibitory effect of SIT-induced IgG [111]. …”
Section: Inhibition Of Basophil/mast Cell Degranulation By Blocking Amentioning
confidence: 99%